Low-income groups and living environment in the cities of the Republic of Malawi. A direct survey about formal and informal settlements (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
After a direct survey, the purpose of this study is to provide elements for a discussion on how to explore sustainable systems in the main cities of the Republic of Malawi (Lilogwe, Blantire, Mzuzu) where the current situation, the historical background and the challenges present typical coexisting cases of formal and informal settlements. The study explores how to improve upgrading systems within Sub-Saharan Africa cities. Over 60% of the population in Malawi lives in informal settlements and experiments the deterioration of the living environment due to rapid urbanization. Through direct surveys in informal settlements and in high-density housing areas, comparative analysis by maps and satellite photographs, bibliographic survey and interviews, the study tries to propose a method for sustainableÂ living environments, housing supply systems, city planning guidelines, building systems.Â